Isolated endobronchial juvenile xanthogranuloma: a case report - Sosnowska, Patrycja; Antosik, Patrycja; Ostałowska, Anna; Nogal, Piotr; Mańkowski, Przemysław (Contemporary Oncology/Współczesna Onkologia, 2020)
Juvenile xanthogranuloma (JXG) is a rare non-Langerhans cell tumour usually diagnosed during infancy. The lesion is typically located in the skin; however, extracutaneous lesions have been described. The symptoms vary depending on the location and size of the lesion. Presented here is a case of 13-year-old girl with this type of tumour located within the bronchus. She reported chest discomfort, difficulty breathing, and cough. A month prior to admission she had suffered from a respiratory tract infection. Prolonged surgical treatment was required due to the tumour’s atypical location and recurrence of the tumour following initial resection. Isolated pulmonary JXG is an extremely rare finding, which requires accurate diagnosis and careful planning of therapeutic treatment. Severe pulmonary symptoms, inconclusive histopathological examination, malignancy risk, and large tumour size are indications for radical surgical resection of the tumour. Non-surgical treatment with chemotherapy is useful in cases of inoperable tumours.